Microplastic removal in field-scale and in-situ water treatment systems: A systematic performance review - Asfandyar Shahab; Licheng Peng; Abubakr M. Idris; He Xiao; Tauseef Ahmad; Yating Luo; Michael S. Bank (Process Safety and Environmental Protection, 2026)

Combining expression optimization and protein engineering for high-level production of protein-glutaminase in Bacillus licheniformis - Asfandyar; Ruibin Zhang; Shuai Zhao; Ali Raza Ishaq; Penghui He; Yi Rao; Dongbo Cai; Shouwen Chen (Food Bioscience, 2026)

Retraction notice to “Influence of hydrothermal treatment on selenium emission-reduction and transformation from low-ranked coal” [J. Clean. Prod. 267 (2020) 122070] - Habib Ullah; Baoliang Chen; Asfandyar Shahab; Faiza Naseem; Audil Rashid; LuLun; Balal Yousaf; Sangar Khan (Journal of Cleaner Production, 2026)

Tailoring of Cerium Oxide Nanosheets Having Superior Peroxidase Catalytic Activity for Colorimetric Detection of Hydrogen Peroxide - Mohib Ullah; Muhammad Aslam Khan; Sajid Ali; Asfandyar; Zeeshan Tahir; Muhammad Babar Saeed; Vineet Tirth; Ali Algahtani; Ruqia Nazir; Muslim Khan (Journal of Fluorescence, 2026)

Orientin: a natural glycoside with versatile pharmacological activities - Ali Raza Ishaq; Heba A. S. El-Nashar; Ayman M. Al-Qaaneh; Asfandyar; Aneela Bashir; Tahira Younis (Natural Product Research, 2025)

Insecticidal and antibacterial properties of zinc oxide nanoparticles (ZnO-NPs) synthesized from Phoebe zhennan leaf extract - Arshad Ali; Kirshan Chand; Chenghu Liu; Asfandyar; Ali Hassan; Hammad Hassan; Xiaolong Liu; Min Lu (Journal of Asia-Pacific Entomology, 2025)

Potential toxic elements (PTEs) in the surface sediments of the Beibu Gulf, South China Sea: Spatiotemporal variation, geochemical fractionation and ecological risk assessment - Xuewen Yang; Qiongyuan Su; Liangliang Huang; Caixia Wen; Asfandyar shahab; Caiguang Wang; Nan Li; Bin Kang (Marine Environmental Research, 2025)

Metal-organic frameworks for targeted capture of Micro/Nanoplastics in aquatic systems: Mechanisms, innovations, and environmental applications - Kaiqiang Xu; Asfandyar Shahab; Jieyue Li; Dunqiu Wang; Abubakr M. Idris; He Xiao (Journal of Water Process Engineering, 2025)

Enhancing municipal sludge composting efficiency: The synergistic impacts of montmorillonite and coconut shell biochar additives on heavy metal passivation and microbial community succession - Wanxuan Qin; Asfandyar Shahab; Xiaojie Sun; Jieyue Li; Kemeng Li; He Xiao (Journal of Environmental Chemical Engineering, 2025)

Overexpressing Endopeptidase Inhibitor IseA Enhances Biomass and Biochemical Production of Bacillus licheniformis - Yongjia Zhang; Penghui He; Shiying Hu; Ruibin Zhang; Asfandyar; Shouwen Chen (Current Microbiology, 2025)

A highly efficient and recyclable zirconium-based metal organic framework for the effective removal of nanoplastics from multiple aqueous environments - Kaiqiang Xu; Asfandyar Shahab; Jieyue Li; Dunqiu Wang; Yanhong Li; Abubakr M. Idris; He Xiao (Process Safety and Environmental Protection, 2025)

Occurrence and health risk of legacy and emerging halogenated flame retardants in seafood from the Beibu Gulf, China - Yanan Cheng; Liang Zhu; Liangliang Huang; Yang Ding; Caiguang Wang; Hao Xu; Qiongyuan Su; Asfandyar Shahab; Bin Kang (Regional Studies in Marine Science, 2025)

Environmental Heavy Metal Exposure and Associated Cardiovascular Diseases in Light of the Triglyceride Glucose Index - Muhammad Bilal Sardar; Mohsin Raza; Ammara Fayyaz; Muhammad Asfandyar Nadir; Zain Ali Nadeem; Muhammad Babar (Cardiovascular Toxicology, 2024)

Interspecific differences in ecological stoichiometric characteristics of invertebrates and their influencing factors from the Beibu Gulf, China - Caiguang Wang; Liangliang Huang; Bin Kang; Liang Zhu; Hao Liu; Shuwen Zhao; Yanan Cheng; Asfandyar Shahab; Yunrong Yan (Frontiers in Marine Science, 2024)
Invertebrates can store carbon (C), nitrogen (N), phosphorus (P), and other elements in their body tissues at theoretically homeostatic rates, thus playing an important role in the biogeochemical cycle of aquatic ecosystems. To sustain homeostasis, consumers must either balance their resource supply or adjust their stoichiometric features in response to environmental changes. However, there is limited understanding regarding potential differences in the ecological stoichiometric characteristics of marine invertebrates. To explore the ecological stoichiometric characteristics of marine invertebrates, the C, N, P, calcium (Ca), δ 13 C, and δ 15 N contents of 18 invertebrate species were analyzed from the Beibu Gulf. The results revealed that the ranges of elemental variations (C, N, and P) in invertebrates were 25.17%-47.34%, 6.14%-14.13%, and 0.26%-1.31%, respectively. The content of P in invertebrates exhibited the most significant variation, leading to alterations in C:P and N:P ratios. A significant negative correlation was observed between P content and body weight in invertebrates ( p < 0.01). Furthermore, the C and N content of invertebrates were significantly negatively correlated with δ 13 C ( p < 0.01), suggesting that the variations in C content and N content in invertebrates are influenced by different food sources, while P content varies according to body size. Our results also indicated significant interspecific differences in the ecological stoichiometry of invertebrates from the Beibu Gulf ( p < 0.05). Invertebrate growth may be inhibited by P, and they do not maintain strict homeostasis, with stable homeostasis observed in higher trophic levels.

High-efficient removal of methylene blue by zirconium-based organic frameworks modified with 1,3,5-benzenetricarboxylic acid: Characterization, performances, and mechanisms - Jinxiong Chen; Xiaozhe Hu; Liangquan Lu; Asfandyar Shahab; Hua Zhang; Shehnaz; Zhenlin Mo; Merfat S. Al-Sharif (Chemosphere, 2024)

Calcined MgFe layered double hydroxides for magnetic separation and enhanced adsorption performance of methyl orange: Mechanism based on the memory effect - Liangquan Lu; Zhenyu Wu; Jianhong Bi; Hua Zhang; Asfandyar Shahab (Journal of Water Process Engineering, 2024)

Occurrence and fate of N-nitrosamines in full-scale domestic wastewater treatment plants and their impact on receiving waters along the Lijiang River, China - Yingjie Chen; Honghu Zeng; Huanfang Huang; Litang Qin; Shihua Qi; Haixiang Li; Asfandyar Shahab; Hao Zhang; Wenwen Chen (Journal of Hazardous Materials, 2024)

Long-term phytoextraction potential and mechanism of Celosia argentea on soils with different levels of Cd and Mn co-contamination - Guo Yu; Habib Ullah; Hua Lin; Geoffrey I. Sunahara; Xuehong Zhang; Baoliang Chen; Hongwei Yu; Asfandyar Shahab; Liheng Liu; Jie Liu (Journal of Environmental Chemical Engineering, 2024)

A critical review on selenium removal capacity from water using emerging non-conventional biosorbents - Habib Ullah; Baoliang Chen; Audil Rashid; Ruohan Zhao; Asfandyar Shahab; Guo Yu; Ming Hung Wong; Sangar Khan (Environmental Pollution, 2023)

Levels and health risk assessment of potential toxic elements in three dominant fish species from the Beibu Gulf, South China Sea - Qiongyuan Su; Caiguang Wang; Liangliang Huang; Asfandyar Shahab; Jiayang He; Yanan Cheng; Hao Xu; Yunrong Yan; Bin Kang (Marine Pollution Bulletin, 2023)

Compost-derived humic and fulvic acid coupling with Shewanella oneidensis MR-1 for the bioreduction of Cr(Ⅵ) - Kemeng Li; Asfandyar Shahab; Jieyue Li; Hongwei Huang; Xiaojie Sun; Shaohong You; Huijun He; He Xiao (Journal of Environmental Management, 2023)

Cadmium uptake and membrane transport in roots of hyperaccumulator Amaranthus hypochondriacus L. - Mengxuan Han; Habib Ullah; Huan Yang; Guo Yu; Shaohong You; Jie Liu; Baoliang Chen; Asfandyar Shahab; Vasileios Antoniadis; Sabry M. Shaheen; Jörg Rinklebe (Environmental Pollution, 2023)

A critical analysis of sources, pollution, and remediation of selenium, an emerging contaminant - Habib Ullah; Lu Lun; Audil Rashid; Noor Zada; Baoliang Chen; Asfandyar Shahab; Ping Li; Muhammad Ubaid Ali; Siyi Lin; Ming Hung Wong (Environmental Geochemistry and Health, 2023)

A comprehensive review on pollution status and associated health risk assessment of human exposure to selected heavy metals in road dust across different cities of the world - Asfandyar Shahab; Zhang Hui; Saeed Rad; He Xiao; Jamil Siddique; Liang Liang Huang; Habib Ullah; Audil Rashid; Mohd Raihan Taha; Noor Zada (Environmental Geochemistry and Health, 2023)

Integrated transcriptome and metabolome analysis reveals the mechanism of tolerance to manganese and cadmium toxicity in the Mn/Cd hyperaccumulator Celosia argentea Linn - Guo Yu; Habib Ullah; Xinshuai Wang; Jie Liu; Baoliang Chen; Pingping Jiang; Hua Lin; Geoffrey I. Sunahara; Shaohong You; Xuehong Zhang; Asfandyar Shahab (Journal of Hazardous Materials, 2023)

Morphological characterization, hazardous metal contamination, source identification, and health risk assessment of the fine road dust from Dachang mining area, China - He Xiao; Jieyue Li; Asfandyar Shahab; Liming Deng; Zahid Ullah; Habib Ullah (Environmental Science and Pollution Research, 2023)

A comprehensive study of potentially toxic element contamination and source quantitative assessment by positive matrix factorization model: risk from the fine road dust of Chehe mining area, China - Jieyue Li; Liming Deng; Shaohong You; He Xiao; Kemeng Li; Asfandyar Shahab (Environmental Science and Pollution Research, 2023)

Arsenic Contamination, Water Toxicity, Source Apportionment, and Potential Health Risk in Groundwater of Jhelum Basin, Punjab, Pakistan - Zahid Ullah; Abdur Rashid; Junaid Ghani; Muhammad Afnan Talib; Asfandyar Shahab; Lu Lun (Biological Trace Element Research, 2023)

Spatial and temporal variation of dissolved heavy metals in the Lijiang River, China: implication of rainstorm on drinking water quality - Liming Deng; Asfandyar Shahab; He Xiao; Jieyue Li; Saeed Rad; Jinping Jiang; GuoYu; Pingping Jiang; Hongwei Huang; Xiangkui Li; Bilal Ahmad; Jamil Siddique (Environmental Science and Pollution Research, 2021)

Volatilization characteristics of selenium during conventional and microwave drying of coal slime: an emerging contaminant in mining industry - Habib Ullah; Asfandyar Shahab; Audil Rashid (Environmental Science and Pollution Research, 2020)

Arsenic contamination, subsequent water toxicity, and associated public health risks in the lower Indus plain, Sindh province, Pakistan - Asfandyar Shahab; Shihua Qi; Muhammad Zaheer (Environmental Science and Pollution Research, 2019)